A Novel Fully Integrated ULV SC DC-DC Converter for Indoor Light Energy Harvesting - da Silva, Luiz; Severo, Lucas Compassi; Girardi, Alessandro (Symposium on Integrated Circuits and Systems Design (SBCCI), 2020)
Indoor energy harvesting using small photovoltaic (PV) cells is still not widely exploited. It can be a solution to supply ultra-low power (ULP) devices for Internet of Things (IoT) applications. However, a PV cell may suffer shading caused by walls, furniture, and human movements. This requires an efficient conversion system that can adapt to voltage variations, demanding a specific adjustable DC-DC converter. The present work aims to propose a fully integrated conversion system for indoor photovoltaic energy harvesting capable to provide a range of voltage conversion ratios (VCRs) suitable for ULP and ultra-low voltage (ULV) applications. The proposed converter is based on a reconfigurable switched-capacitor (SC) topology. A systematic simulation-based methodology for designing the DC-DC converter is presented, including switches and capacitors sizing and operating frequency optimization. Results show that the proposed circuit can obtain 19 different VCRs with an estimated peak efficiency of 94.26%. This is an important step towards a practical self-powered indoor system for IoT applications.